Comparison of Pain Scale, Hemodynamics, and Side Effects of Percutaneous and Intravenous Fentanyl in Post Sectio Caesaria Patients at Bunda Hospital - Annisa`'a Nurillah Moesthafa; Achmad Riviq Said; Ros Sumarny; Yati Sumiyati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This is novel research about comparison pain scale, hemodynamics, and side effects of percutaneous and intravenous fentanyl in post sectio cesarean patients. Sectio cesarean is a method of delivering a fetus through an incision in the abdominal wall (laparotomy) and the uterus wall. This method induces pain in the incision, so patients feel complicated or afraid to mobilize. Fentanyl is one of the opioid analgesics, which is the main choice in section caesarian surgery because safe for breastfeeding, is more potent than morphine, and acts as balanced anesthesia—comparing the use of percutaneous fentanyl with intravenous fentanyl with pain scale parameters, hemodynamics, and side effects in sectio caesarian patients at Bunda Mother and Child Hospital Jakarta. Before conducting this research, an observational study first makes an ethical approval. Data were taken prospectively and collected simultaneously to compare percutaneous and intravenous fentanyl performed on post sectio cesarean patients with the physical status of the American Society of Anesthesiologists (ASA) I–II at Bunda Mother and Child Hospital Jakarta from September to November 2020. Comparative data observed were pain scale parameters, hemodynamics, and side effects after percutaneous fentanyl therapy or intravenous fentanyl therapy. Data were processed using SPSS 22 version and Microsoft Excell 2016. In conclusion, intravenous fentanyl is more effective in reducing pain scale and has more minor side effects than percutaneous fentanyl. There is no significant difference in hemodynamic parameters (p-value >0.05).